META- ANALYSIS OF THE USE MOVIE TRAILER IN EFL CLASSROOMTHE EFFECT OF THE READER’S THEATER TECHNIQUE ON THE ENGLISH STUDENTS’ SPEAKING ACHIEVEMENT AT STKIP PGRI JOMBANG - Muhammad Farhan Rafi; Aang Fatihul Islam (STKIP PGRI Jombang, 2018)
The objective of speaking class is to improve and develop students’ speaking skill to be fluent, correct and accurate. One of techniques applied on that speaking class is Reader’s Theatre. Reader’s theatre can encourage students to speak English fluently with correct vocabulary, pronounce words well and speak with a good structure. This study aims to know the effectiveness from reader’s theatre toward students’ speaking skill at STKIP PGRI Jombang. The population of this study is all students of 2017 English department while the samples are 2017 A students and 2017 B students. The research design applies quasi experiment with a test as the instrument and calculate the data with ANCOVA. It shows that the significant value is 0,003, it is lower than the significant level 0,05. The result of the study shows that there is a significant effect to reader’s theatre on students’ speaking skill at STKIP PGRI Jombang and reader’s theatre can give a good result on students’ speaking skill.